Religious Attendance Serves as a Protective Variable Against Suicidal Ideation During Treatment - Price, Samantha (Pastoral psychology, 2017)
Several studies have proposed potential mediators of the association between religion and mental health, including social support (SS), locus of control (LOC), and substance abuse (SA), but have been limited by their use of non-clinical samples. The current study, therefore, drew from a clinical sample at risk of violence to self to test associations among these variables, specifically examining the effect of these variables on the relation between religious attendance (RA) and suicidal ideation (SI). A total of 144 adult outpatient psychotherapy clients evidencing SI during treatment were assessed pre-treatment for diagnostic presentation and frequency of RA. Subsequently, before each therapy session, SI, SS, SA, and external LOC (eLOC) during the preceding week were assessed via self-report. RA exerted a significant direct effect on SI within this clinical sample, with increased attendance associated with decreased SI. In contrast to prior reports based on non-clinical samples, SS, SA, or eLOC did not mediate the association of RA to SI. However, these variables did work in tandem, independent of RA, to affect SI. Findings support prior research suggesting that focusing on SS, SA, and LOC may be beneficial to clients experiencing SI. Additionally, for those clients who hold religious practices as a personal value, incorporating discussion of RA may help thwart SI.